SPE Annual Technical Conference and Exhibition 2003
DOI: 10.2118/84075-ms
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Reuse of the Produced Chemicals in Alkaline-Surfactant-Polymer Floods

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractAlkaline-Surfactant-Polymer (ASP) flood processes have been increasingly applied in the oil fields due to their high ultimate oil recovery. However, a major technical challenge is how to significantly reduce the amount and the cost of chemicals used such that ASP floods can become cost-effective as well. On the other hand, field applications show that the concentrations of alkali, surfactant and polymer remain relatively high in the produced fluids of ASP flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“… Additional quantity of produced oil added to the quantity of oil produced from the pilot though water flooding is: 71211.5m 3…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Additional quantity of produced oil added to the quantity of oil produced from the pilot though water flooding is: 71211.5m 3…”
Section: Discussionmentioning
confidence: 99%
“…This operation can be applied with an increase in the cost of producing one barrel ranges between (1.6-3.5 $/bb). Moreover, researchers Gu and Wang [3], through their experiments, showed that concentrations of polymers, surfactants, and alkaline remain high in the produced fluids when ASP method is applied, therefore, the successful study of these chemicals can dramatically reduce cost of this operation. Also, In a pilot experiment on injecting ASP solution in Daqing oil field, researchers Ang and Huabin [4] evaluated performance of the experiments by achieving the following results: Average of oil production increased in the experiment area from (36.7m3/day) to (91.5 m3/day), while percent of the produced oil decreased from (82.7%) to (59.7%).…”
Section: Reference Studiesmentioning
confidence: 99%
“…Thus, ASP can have reduced the cost of the operation, and any loss is due to the adsorption or chemical reaction with the oil. [8] According to Huabin& Shutang, the daily production rate of oil increased from 36.7 m3/day to 91.5 m3/day during a pilot test using ASP in Daqig field, while the water cut decrease from 82.7% to 59.7%. in addition, the daily production rate increased from 3.7 m3/day to 27.1 m3/day in the well surrounded by injectors (5-Spot)and water cut decrease from 87.9% to 45.8% .…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, sufficiently high amount of alkaline should be injected to compensate the consumption of alkaline by the acidic component; divalent ions in the aqueous; and ion-exchange. Including the alkaline in the SP process makes the process cost-efficient not only through generating the soap but also the injected alkali can significantly decrease the surfactant (Wanchao et al, 1995;Al-Hashim et al, 1996;Wang and Gu, 2003;Hirasaki et al, 2004;Liu et al, 2008;Liu, 2008;Mohan, 2009;Sheng, 2013) and polymer (Wanchao et al, 1995) adsorptions to the rock, alter the wettability of the rock (Wyatt et al, 2002;Wang and Gu, 2003;Liu, 2008;Sundstrom, 2011;Sheng, 2013;Fortenberry et al, 2013), and accelerate the equilibrium time, shortening the coalesce time (Jackson, 2006). The dilemma involved in the AP process makes the process impractical most of the times.…”
Section: Introductionmentioning
confidence: 99%